PERANAN GURU BIMBINGAN DAN KONSELING DALAM MEMBENTUK KARAKTER MELALUI MATA PELAJARAN AL-ISLAM DAN KEMUHAMMADIYAHAN DI SMK MUHAMMADIYAH 3 BANJARMASIN - Rezki Rahmah (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2017)
Background problem in this research is the need for the formation of character or morality so that students directed behavior and good manners. In this current phenomenon of increasing juvenile delinquency. Hence the formation of character done by teachers especially religious teachers such as Al-Islam and Kemuhammadiyahan and teachers Guidance and Counseling. The purpose of this study was to determine what the role of the teacher Al-Islam and Kemuhammadiyahan as well as guidance and counseling teachers to shape the character or good character for students.This study uses a qualitative research design with descriptive research. Source data used are primary data in the form of interviews with the principals, teachers BK, a teacher of Al-Islam and Kemuhammadiyahan, and five students of SMK Muhammadiyah 3 Banjarmasin, while secondary data in the form of photographs and documents from the school, with the technique observation, interviews and documentation. Data analysis was performed with data reduction, data display. Test the validity of test data using kreadibilitas. Kreadibilitas test used was triangulation source.The results of this study indicate that Al-Islam and Kemuhammadiyan have an equally important role with teacher guidance and counseling. Teacher Al-Islam and Kemuhammadiyahan provide materials such as understanding a sura of the Al-Qur’an and in the matter is expected to form a good character for students as a religious attitude, honesty and tolerance. This was done outside the classroom as midday prayers in congregation, read al-Quran, listen to religious lectures and it was not separated from the teacher guidance and counseling.